Vitamin D Deficiency Mimicking Pseudohypoparathyroidism Type II in an Adolescent Boy: A Case Report - Shieh, Andrew; Alvarez, Griselda (International Journal of Clinical Research, 2022)
Background: Vitamin D deficiency in children is common and usually characterized by hypocalcemia, hypophosphatemia, and elevated serum parathyroid hormone level. However, vitamin D deficiency can be associated with parathyroid hormone resistance in the kidneys which may cause hyperphosphatemia instead, mimicking thus pseudohypoparathyroidism type II. The exact pathogenesis for parathyroid hormone resistance remains unclear, and the distinction between the two conditions remains difficult. We describe the case of an adolescent who presented with seizures and was found to have biochemical features consistent with pseudohypoparathyroidism, likely related to vitamin D deficiency. Case Report: A 13-year-old previously healthy adolescent presented with seizures. He experienced back pain during the previous month prior to the presentation. He did not have features of Albright hereditary osteodystrophy. His laboratory studies were significant for hypocalcemia, hyperphosphatemia, elevated serum alkaline phosphatase level, elevated parathyroid hormone level, and a deficient vitamin D level. Magnetic resonance imaging of the spine revealed multiple compression fractures. The child was treated with intravenous calcium and vitamin D administration with rapid improvement and his seizures resolved. Conclusion: Hypocalcemia from vitamin D deficiency can mimic pseudohypoparathyroidism type II. The principles of treatment for hypocalcemia in both conditions are similar and patients require timely intervention with close follow-up to ensure the resolution of symptoms. Patients with resolution of symptoms after adequate treatment may not require further evaluation for other types of pseudohypoparathyroidism.